ANALISIS KUALITAS PRODUK, CITRA MEREK DAN VARIASI PRODUK TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN PADA KONSUMEN BRAND SKINCARE SOMETHINC DI KOTA PEKANBARU - Suchita, Natasya Baby; Zulkarnain, Zulkarnain; Halim, Edyanus Herman (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
The beauty industry in Indonesia is growing very rapidly. This has resulted in increasingly fierce competition in the cosmetics business, especially skincare cosmetics. One type of skincare product that is popular and much favored by women in Indonesia is serum. Somethinc is one of the many brands that produce serum type skincare products. This study aims to analyze the effect of Product Quality, Brand Image and Product Variety on Purchase Intention and Purchase Decision of Somethinc Skincare Brand in Pekanbaru City, both direct influence and indirect influence. The population in this study are consumers of skincare brand Somethinc serum type who have bought these products and have used Somethinc skincare products serum type in Pekanbaru city. The sampling technique used is the Non-Probability Sampling method with Purposive Sampling, obtained a sample size of 213 respondents, namely consumers of skincare brand Somethinc serum type who live in Pekanbaru City as respondents in this study. This study uses Structural Equation Modeling (SEM) data analysis techniques using SmartPLS software assistance. With Descriptive Statistical Analysis of Measurement Model Evaluation (Outer Model) & (Inner Model) and hypothesis testing. The results of this study indicate that Product Quality, Brand Image, Product Variety and Purchase Intention have a direct influence on Purchasing Decisions. The sobel test results show that there is an indirect effect on Product Quality, Brand Image and Product Variety on Purchasing Decisions through Purchase Intention.